Integrated silicon qubit platform with single-spin addressability, exchange control and single-shot singlet-triplet readout - M. A. Fogarty; K. W. Chan; B. Hensen; W. Huang; T. Tanttu; C. H. Yang; A. Laucht; M. Veldhorst; F. E. Hudson; K. M. Itoh; D. Culcer; T. D. Ladd; et al. (Nature Communications, 2018)
Significant progress has been made developing the different methods needed for a spin-based quantum computer but the challenge of integrating them remains. Fogarty et al. present a system with single-spin addressability, spin-spin interactions and high-fidelity readout that provides a scalable foundation for error-corrected devices.